Relevance of elevated microparticles in peripheral blood and synovial fluid of patients with rheumatoid arthritis - Benita N R Michael; Durga Prasanna Misra; K G Chengappa; Vir Singh Negi (Indian Journal of Rheumatology)
Introduction: Microparticles (MPs) are submicron sized heterogeneous membrane-bound vesicles released from cells undergoing cell activation or apoptosis. Elevated platelet-derived MPs (PMPs) are reported in rheumatic diseases. We profiled Annexin-V+ MPs and CD61+ MPs in plasma and synovial fluid of patients with rheumatoid arthritis (RA) and their clinical correlates. Methods: Twenty-three newly diagnosed disease-modifying anti-rheumatic drug naïve patients with RA, 17 with osteoarthritis (OA) and 22 healthy controls (HC) were enrolled. Five milliliters of synovial fluid from the knee joint of patients with RA and OA was collected; 5 ml of peripheral blood was collected from patients with RA, OA, and HC. Cell-free synovial fluid and platelet poor plasma samples were stained with Annexin-V-APC and Anti-CD61-BV510 antibodies followed by flow cytometry analysis (FACSAria III) (results expressed as the mean ± standard deviation of % population). Results: Significantly greater levels of synovial fluid MPs (Annexin-V+ MPs) were observed in RA versus OA (P < 0.0001), significantly higher synovial fluid PMPs (Annexin V+ CD61+ MPs) levels in RA compared to HC (P = 0.0472). MPs other than those of platelet origin (Annexin V+ CD61− MPs) were also increased in the synovial fluid of RA patients compared to OA (P < 0.0001). Kruskal–Wallis test revealed the significant difference in the levels of plasma MPs (Annexin-V+), PMPs (Annexin V+ CD61+ MPs), and MPs other than those of platelet origin (Annexin V+ CD61− MPs) between RA, OA, and HC groups (P < 0.0001) with a higher percentage in RA group. Conclusions: Higher levels of Annexin-V+ MPs in both plasma and synovial fluid of RA suggest a role for MPs in the pathogenesis of RA. Elevated plasma PMPs (Annexin V+ CD61+ MPs) in RA may suggest their role in systemic involvement. Furthermore, increased levels of MPs other than those of platelet origin (Annexin V+ CD61− MPs) indicate the necessity to study the MPs from other cell lineages.